PENAMBAHAN KUNING TELUR ITIK DALAM PENGENCER NACL FISIOLOGIS TERHADAP KUALITAS SEMEN AYAM KAMPUNG YANG DISIMPAN PADA SUHU RUANG - Angelina Novita Tethool; Hasril Hasril; Johan F. Koibur; M. Jen Wajo; Isti Widayati; Noveling Inriani (Maduranch : Jurnal Ilmu Peternakan dan Ilmu Agribisnis, 2026)
This study aimed to investigate the effect of storage duration with the addition of duck egg yolk on the quality of Kampung chicken spermatozoa stored at room temperature. The roosters used were 18–20 months old with a body weight ranging from 1.8 to 2.1 kg. A factorial completely randomized design (CRD) was employed, consisting of two factors. The first factor was the type of semen diluent: 100% physiological NaCl (P0), 95% physiological NaCl + 5% duck egg yolk (P1), 90% physiological NaCl + 10% duck egg yolk (P2), and 85% physiological NaCl + 15% duck egg yolk (P3). The second factor was the storage duration at room temperature (25–28°C): 30 minutes (A1), 60 minutes (A2), 90 minutes (A3), and 120 minutes (A4). Data were analyzed using a factorial CRD, and if a significant effect was observed (P < 0.05), further analysis was conducted using Duncan’s Multiple Range Test (DMRT). The results demonstrated that the use of physiological NaCl supplemented with duck egg yolk in all treatments (P0, P1, P2, and P3) maintained average sperm motility and viability above 70%, and abnormality rates below 20%. Storage at room temperature for up to 90 minutes preserved sperm motility and viability above 70%, with abnormalities remaining under 20%. A highly significant interaction (P<0.01) was observed between the type of diluent and storage duration at room temperature for sperm motility and viability. However, no significant interaction was found for sperm concentration and abnormality.Keywords: Duck Egg Yolk, Kampung chicken, Semen diluent, Spermatozoa